EVALUASI IMPLEMENTASI SISTEM PENDAFTARAN ONLINE TERHADAP KEPUASAN PASIEN DI PUSKESMAS KEMAYORAN TAHUN 2023 - Fathia Nurul Izza (2023)
Several obstacles were encountered during the implementation of online registration, including lack of community involvement, incomplete list of poly in the application, limited counter officers, and others. This study aims to evaluate the implementation of an online registration system on patient satisfaction using the End User Computing Satisfaction method at Puskesmas Kemayoran. The study used a cross-sectional design. Data collection used questionnaires to 172 online registration patients. This study used the chi-square test and its alternatives to analyze the relationship of each variable. The results showed that age (p = 0.999), gender (p = 1.000), education level (p = 1.000), and employment (p = 0.633) had no relationship with patient satisfaction, while the content (p = 0.046), accuracy (p = 0.002), format (p = 0.000), ease of use (p = 0.000), and timeliness (p = 0.006) had a relationship with patient satisfaction. The conclusion of this study is that there is no relationship between individual characteristics and patient satisfaction and there is a relationship between EUCS dimensions and patient satisfaction. It is recommended for Puskesmas Kemayoran to conduct periodic evaluations, convey patient complaints to related parties to improve application quality, simplify the online registration flow, and increase the number of registration counter officers.